2017
DOI: 10.1182/blood-2016-10-747170
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fatal bleeding during induction therapy for acute promyelocytic leukemia in the ATRA era

Abstract: • High WBC is an independent predictor of early HD in APL.Acute promyelocytic leukemia (APL) is commonly complicated by a complex coagulopathy. Uncertainty remains as to which markers of bleeding risk are independent predictors. Drawing from 5 large clinical trials that included all-trans retinoic acid (ATRA) as part of induction, we assessed known determinants of bleeding at baseline and evaluated them as potential predictors of hemorrhagic death (HD) in the first 30 days of treatment. The studies included we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 29 publications
4
33
1
Order By: Relevance
“…In multicenter studies, the most frequent causes of death were identified as bleeding, differentiation syndrome, infection, and multiorgan failure. Cerebral hemorrhage and severe infection are generally involved in early deaths, which primarily occur in patients with hyperleukocytosis [ 245 ]. Delays in ATRA therapy have been suggested as a contributing factor to early deaths [ 246 ], as has initial hospitalization in nonspecialized primary care institutions [ 241 , 247 ].…”
Section: Discussionmentioning
confidence: 99%
“…In multicenter studies, the most frequent causes of death were identified as bleeding, differentiation syndrome, infection, and multiorgan failure. Cerebral hemorrhage and severe infection are generally involved in early deaths, which primarily occur in patients with hyperleukocytosis [ 245 ]. Delays in ATRA therapy have been suggested as a contributing factor to early deaths [ 246 ], as has initial hospitalization in nonspecialized primary care institutions [ 241 , 247 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, high-risk APL (defined by a white blood cell count $10 3 10 3 /mL) has been associated with increased risks of early hemorrhagic death and relapse. 1,2 Although arsenic trioxide (ATO)-based regimens have clearly improved outcomes for patients with standard-risk APL, 3,4 their effects on patients with high-risk APL are less clear. Recent trials from both the North American Intergroup Study and the Medical Research Council have confirmed the benefit of ATO as frontline therapy for patients with APL and have reported similar outcomes among smaller high-risk subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…High WBC, high peripheral blast count, M3v and black ethnicity were independent predictors of early hemorrhagic death in several studies. 19 , 29 However, our patients who died due to early ICH had low WBC counts (1.8 and 2.6 ×10 3 /μL), and their peripheral blast percentages were also low (10 and 58%, Table 2 ). Hypogranular APL patients of our cohort did not have severe hemorrhagic complications.…”
Section: Discussionmentioning
confidence: 67%